Asphalt-based porous hard carbon material as well as preparation method and application thereof
By mixing coal asphalt, petroleum asphalt and catalyst to form a composite matrix and carbonize it, asphalt-based porous hard carbon materials with low graphitization are prepared, which solves the problem that porous hard carbon materials are not conducive to sodium ion storage after coal asphalt heat treatment, and achieves the effect of improving sodium ion storage capacity and battery cycle stability.
Patent Information
- Application Number
- CN202510191021.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-05-02
AI Technical Summary
The porous hard carbon material obtained by heat treatment of coal asphalt has high degree of graphitization and few defects, which is not conducive to sodium ion storage.
By mixing coal asphalt, petroleum asphalt and p-toluenesulfonic acid as catalysts, carbonize the composite matrix to prepare asphalt-based porous hard carbon material with low graphitization and large layer spacing.
The specific surface area of porous hard carbon material is improved, the transport of ions and the immersion of electrolyte are enhanced, and the physical effective contact area between the electrode material and the electrolyte is increased, thereby improving the storage capacity of sodium ions and the cycling stability of the battery.
Smart Images

Figure CN119911896A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and more specifically, to an asphalt-based porous hard carbon material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background section is intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Countries around the world are constantly increasing the development and utilization of renewable energy such as solar energy and wind energy. However, due to the intermittent and unstable nature of renewable energy, it has become increasingly urgent to develop efficient and economical energy storage and conversion systems. Lithium-ion batteries with graphite as the negative electrode material have been widely used in various fields of people's lives, especially in portable electronic devices, due to their high energy density and long cycle life. However, the rapid development of electronic devices and electric vehicles has further increased society's energy demand and also put forward higher requirements for energy storage systems. Lithium-ion batteries are about to reach the limit of their energy density. Therefore, it has become one of the most promising next-generation electrochemical energy storage systems with a similar mechanism to ion batteries and abundant sodium source reserves.
[0004] The lack of high-capacity negative electrode materials has hindered the further development of sodium-ion batteries. Coal tar pitch is a black block at room temperature. Its main components are complex polycyclic aromatic hydrocarbons, condensed aromatic hydrocarbons and their derivatives. Its high carbon content and low price make it an ideal negative electrode material for sodium ions. However, during the heat treatment process of coal tar pitch, due to the π-π interaction between aromatic hydrocarbons, almost parallel stacked carbon sheets are often formed, with fewer defects and a higher degree of graphitization, which hinders the storage of sodium ions. Summary of the invention
[0005] The present application is provided to solve the above defects in the prior art. A pitch-based porous hard carbon material and its preparation method and application are needed to solve the problem that the porous hard carbon material obtained by heat treatment of coal pitch has a high degree of graphitization and few defects, which is not conducive to the storage of sodium ions.
[0006] In the first aspect of the present application, a method for preparing an asphalt-based porous hard carbon material is provided, the preparation method comprising: mixing coal tar, petroleum asphalt and a catalyst to obtain a mixed asphalt, wherein the catalyst is p-toluenesulfonic acid, and then carbonizing the mixed asphalt to obtain an asphalt-based porous hard carbon material.
[0007] In a second aspect of the present application, there is provided a pitch-based porous hard carbon material obtained by the method for preparing the pitch-based porous hard carbon material described in any embodiment of the present application.
[0008] The third aspect of the present application provides an application of the asphalt-based porous hard carbon material described in any embodiment of the present application in a sodium ion battery.
[0009] In a fourth aspect of the present application, a sodium ion battery is provided, characterized in that the sodium ion battery comprises a positive electrode, a negative electrode, a diaphragm and an electrolyte, the negative electrode comprises the asphalt-based porous hard carbon material described in any embodiment of the present application; the diaphragm comprises glass fiber or a polypropylene microporous membrane; the electrolyte comprises sodium hexafluorophosphate or sodium perchlorate; and the positive electrode is sodium metal.
[0010] The various embodiments of the present application provide an asphalt-based porous hard carbon material and a preparation method and application thereof, which utilize coal tar and petroleum asphalt as raw materials and para-toluenesulfonic acid as a catalyst to promote the formation of a composite matrix through catalytic cross-linking between coal tar molecules and petroleum asphalt molecules, i.e., an acid-base condensation reaction occurs, thereby suppressing the π-π interaction between aromatic hydrocarbons during the carbonization of the mixed asphalt. The composite matrix is carbonized to obtain a porous hard carbon material, and the obtained porous hard carbon material has a low degree of graphitization and a large interlayer spacing. In addition, the method for preparing a porous hard carbon material of the present application has simple steps, mild conditions, and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.
[0012] Figure 1 The XRD diagrams of the asphalt-based porous hard carbon material prepared according to Example 1 of the present application and the coal-tar pitch-based carbon material prepared according to Comparative Example 1 are shown; Figure 2 SEM images of the asphalt-based porous hard carbon material prepared according to Example 1 of the present application and the coal tar pitch-based carbon material prepared in Comparative Example 1 are shown, wherein a and b are the coal tar pitch-based carbon materials of Comparative Example 1, and c and d are the asphalt-based porous hard carbon materials of Example 1; Figure 3 The first charge and discharge curves of the batteries prepared according to Example 1, Example 3 and Comparative Example 1 of the present application are shown. DETAILED DESCRIPTION
[0013] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation examples. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation examples, but are not intended to limit the present application.
[0014] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.
[0015] According to an embodiment of the present application, a method for preparing an asphalt-based porous hard carbon material is provided, the preparation method comprising: mixing coal tar, petroleum asphalt and a catalyst to obtain a mixed asphalt, wherein the catalyst is p-toluenesulfonic acid, and then carbonizing the mixed asphalt to obtain an asphalt-based porous hard carbon material.
[0016] Coal tar pitch and petroleum tar pitch are two different asphalts. After coal tar pitch and petroleum tar pitch are mixed, the mixture contains acidic functional groups, basic functional groups and heteroatom functional groups. The catalyst p-toluenesulfonic acid can promote the condensation reaction of acidic functional groups and basic functional groups, cross-link to obtain a composite matrix, inhibit the π-π interaction between aromatic hydrocarbons in the carbonization process of coal tar pitch and petroleum tar pitch, and obtain a porous hard carbon material with a low degree of graphitization and a large interlayer spacing. The specific surface area of the porous hard carbon material is increased, which is more conducive to the transmission of ions and the immersion of electrolytes, and increases the physical effective contact area between the electrode material and the electrolyte.
[0017] The coal tar pitch and petroleum tar pitch of the present application are first formed into a composite matrix and then carbonized. This process is different from the process of directly heat treating and then carbonizing the coal tar pitch and / or petroleum tar pitch.
[0018] In some embodiments, the coal tar pitch, petroleum asphalt and catalyst are mixed and reacted in a solvent, and the solvent is toluene; the product after the mixed reaction is added to glycerol to evaporate the toluene, thereby obtaining a mixed asphalt after the toluene is removed.
[0019] In some embodiments, the mass ratio of the coal tar pitch, petroleum asphalt and p-toluenesulfonic acid is 1 g: (0.2-0.6) g: (0.01-0.03) g. When the amount of the added coal tar pitch and petroleum asphalt remains unchanged and the amount of the added p-toluenesulfonic acid catalyst changes, the battery capacity of the sodium ion battery is affected. When the amount of the added coal tar pitch and p-toluenesulfonic acid remains unchanged and the amount of the added petroleum asphalt changes, the obtained asphalt-based porous hard carbon material is used as the negative electrode of the sodium ion battery, which affects the battery capacity of the sodium ion battery.
[0020] In some embodiments, the coal tar pitch is derived from lignite, bituminous coal or anthracite; the petroleum asphalt is derived from petroleum.
[0021] In some embodiments, the mass volume ratio of mixed asphalt and toluene is 1 g:(10-50) mL.
[0022] In some embodiments, the temperature at which toluene is evaporated is 120-150 °C.
[0023] In some embodiments, the temperature for the mixed reaction of coal tar pitch, petroleum asphalt and catalyst is 50-70 °C; the time for the mixed reaction is 2-6 h.
[0024] In some embodiments, the carbonization is carried out under an inert atmosphere, the carbonization temperature is 900-1300 ° C, the time is 1-4 h, and the heating rate is 3-10 ° C / min. The carbonization temperature and time are conducive to improving the richer pore structure of the porous hard carbon material.
[0025] In some embodiments, the inert atmosphere is argon, nitrogen, a hydrogen-argon mixture, or the like.
[0026] According to an embodiment of the present application, a pitch-based porous hard carbon material obtained by the preparation method of the pitch-based porous hard carbon material described in any embodiment of the present application is also provided. The porous hard carbon material obtained in the present application is composed of irregular micron-sized particles, and the surface is formed by the accumulation of nanoparticles (30-50 nm), and abundant and open pores are formed between the nanoparticles.
[0027] According to the embodiments of the present application, there is also provided an application of the asphalt-based porous hard carbon material described in any embodiment of the present application in a sodium ion battery. As the negative electrode material of the sodium ion battery, the porous hard carbon material can solve the problem that the hard carbon material obtained by heat treatment of coal tar pitch is not conducive to sodium ion storage and the battery capacity is small. It can effectively improve defects and reduce the degree of graphitization, increase the sodium storage capacity, enhance cycle stability, and also expand the spacing between carbon layers to promote fast and efficient electron transfer.
[0028] According to an embodiment of the present application, a sodium ion battery is also provided, characterized in that the sodium ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, and the negative electrode comprises the porous hard carbon material described in any embodiment of the present application.
[0029] In some embodiments, the separator includes glass fiber or polypropylene microporous membrane, etc. Preferably, the separator is glass fiber.
[0030] In some embodiments, the electrolyte includes sodium hexafluorophosphate or sodium perchlorate, etc. Preferably, the electrolyte is sodium hexafluorophosphate.
[0031] In some embodiments, the positive electrode is sodium metal.
[0032] The voltage window range of the sodium ion battery of the present application is 0.01-3 V.
[0033] According to an embodiment of the present application, a method for preparing the sodium ion battery described in any embodiment of the present application is also provided, and the preparation method comprises: 1) mixing the asphalt-based porous hard carbon material, conductive agent, binder and solvent described in any embodiment of the present application to obtain a slurry; coating the slurry on an electrode substrate, and drying to obtain a negative electrode; 2) assembling the negative electrode obtained in step 1) with a positive electrode, a separator and an electrolyte to obtain a sodium ion battery.
[0034] In some embodiments, the drying temperature in step 1) is 50-60 °C and the drying time is 6-24 h. Preferably, the drying is vacuum drying. The solvent in the slurry is removed by vacuum drying, thereby forming an electrode sheet containing a porous hard carbon material on the surface of the copper foil.
[0035] In some embodiments, the conductive agent is carbon black, conductive graphite, carbon tube, graphene, Ketjen black or acetylene black, etc. Preferably, the conductive agent is acetylene black, wherein the carbon black may be Super P (conductive carbon black).
[0036] In some embodiments, the mass ratio of the asphalt-based porous hard carbon material, the conductive agent and the binder in step 1) is 8:(0.8-1.2):(0.8-1.2).
[0037] In some embodiments, the binder is polyvinylidene fluoride (PVDF), styrene-butadiene rubber latex (SBR) or carboxymethyl cellulose (CMC), etc. Preferably, the binder is polyvinylidene fluoride.
[0038] In some embodiments, the solvent is 1-methyl-2-pyrrolidone or water, etc. Preferably, the solvent is 1-methyl-2-pyrrolidone.
[0039] Example 1 1. Preparation of asphalt-based porous hard carbon materials: (1) Preparation of mixed asphalt: Mix 1 g of coal tar and 0.4 g of petroleum asphalt in 20 mL of toluene solution and mix them evenly by ultrasonication for 30 min. Then add 0.02 g of p-toluenesulfonic acid and stir them under magnetic stirring at 50 °C for 2 h. Add the above mixed solution into 50 mL of propylene glycol, heat to 120 °C and stir until toluene is completely evaporated. Finally, vacuum filter, wash with ethanol and deionized water to remove residual toluene and propylene glycol, and dry to obtain the mixed asphalt for use; (2) Preparation of asphalt-based porous hard carbon material: The mixed asphalt obtained in step (1) is placed in a corundum boat, transferred to a tube furnace and heated to 1200 °C at a rate of 2 °C / min under the protection of argon gas, kept at this temperature for 2 h and then cooled to room temperature to obtain the porous hard carbon material. The coal tar pitch used is anthracite.
[0040] 2. Preparation of sodium ion batteries: (1) Grind the asphalt-based porous hard carbon material, acetylene black and binder PVDF prepared in step 1 in a mortar at a mass ratio of 8:1:1, then add 1-methyl-2-pyrrolidone until the powder is a black viscous slurry for later use; (2) Using a 100 μm scraper, the slurry obtained in step (1) is evenly coated on a copper foil, and then the copper foil is dried at 60 ° C for 6 h, and finally punched into a circular electrode sheet with a diameter of 12 mm, which is the negative electrode of the sodium ion battery; (3) The electrode sheet obtained in step (2) is used as the negative electrode, sodium metal is used as the positive electrode, glass fiber is used as the separator, 1MNaPF6 is used as the electrolyte, and the voltage range is 0.01~3 V to prepare a sodium ion battery.
[0041] Example 2 1. Preparation of asphalt-based porous hard carbon materials: (1) Preparation of mixed asphalt: Mix 1 g of coal tar and 0.25 g of petroleum asphalt in 20 mL of toluene solution and mix them evenly by ultrasonication for 30 min. Then add 0.02 g of p-toluenesulfonic acid and stir them under magnetic stirring at 50 °C for 2 h. Add the above mixed solution into 50 mL of propylene glycol, heat to 120 °C and stir until toluene is completely evaporated. Finally, vacuum filter, wash with ethanol and deionized water to remove residual toluene and propylene glycol, and dry to obtain the mixed asphalt for use; (2) Preparation of asphalt-based porous hard carbon material: Same as step (2) in step 1 of Example 1.
[0042] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0043] Example 3 1. Preparation of asphalt-based porous hard carbon materials: (1) Preparation of mixed asphalt: Mix 1 g of coal tar and 0.6 g of petroleum asphalt in 20 mL of toluene solution and mix them evenly by ultrasonication for 30 min. Then add 0.02 g of p-toluenesulfonic acid and stir them magnetically at 50 °C for 2 h. Add the above mixed solution into 50 mL of propylene glycol, heat to 120 °C and stir until toluene is completely evaporated. Finally, vacuum filter, wash with ethanol and deionized water to remove residual toluene and propylene glycol, and dry to obtain the mixed asphalt for use; (2) Preparation of pitch-based porous hard carbon material: Same as step (2) in step 1 of Example 1.
[0044] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0045] Example 4 1. Preparation of asphalt-based porous hard carbon materials: (1) Preparation of mixed asphalt: Mix 1 g of coal tar and 0.4 g of petroleum asphalt in 20 mL of toluene solution and mix them evenly by ultrasonication for 30 min. Then add 0.01 g of p-toluenesulfonic acid and stir them magnetically at 50 °C for 2 h. Add the above mixed solution into 50 mL of propylene glycol, heat to 120 °C and stir until toluene is completely evaporated. Finally, vacuum filter, wash with ethanol and deionized water to remove residual toluene and propylene glycol, and dry to obtain the mixed asphalt for use; (2) Preparation of pitch-based porous hard carbon material: Same as step (2) in step 1 of Example 1.
[0046] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0047] Example 5 1. Preparation of asphalt-based porous hard carbon materials: (1) Preparation of mixed asphalt: Mix 1 g of coal tar and 0.4 g of petroleum asphalt in 20 mL of toluene solution and mix them evenly by ultrasonication for 30 min. Then add 0.05 g of p-toluenesulfonic acid and stir them under magnetic stirring at 50 °C for 2 h. Add the above mixed solution into 50 mL of propylene glycol, heat to 120 °C and stir until toluene is completely evaporated. Finally, vacuum filter, wash with ethanol and deionized water to remove residual toluene and propylene glycol, and dry to obtain the mixed asphalt for use; (2) Preparation of pitch-based porous hard carbon material: Same as step (2) in step 1 of Example 1.
[0048] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0049] Example 6 1. Preparation of asphalt-based porous hard carbon materials: (1) Preparation of mixed asphalt: same as step (1) in step 1 of Example 1; (2) Preparation of asphalt-based porous hard carbon material: The mixed asphalt obtained in step (1) is placed in a corundum boat, transferred to a tube furnace and heated to 1000 °C at a rate of 2 °C / min under the protection of argon gas, kept at this temperature for 2 h and then cooled to room temperature to obtain the porous hard carbon material. The coal tar pitch used is anthracite.
[0050] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0051] Example 7 1. Preparation of asphalt-based porous hard carbon materials: (1) Preparation of mixed asphalt: same as step (1) in step 1 of Example 1; (2) Preparation of asphalt-based porous hard carbon material: The mixed asphalt obtained in step (1) is placed in a corundum boat, transferred to a tube furnace and heated to 1300 °C at a rate of 2 °C / min under the protection of argon gas, kept at this temperature for 2 h and then cooled to room temperature to obtain the porous hard carbon material. The coal tar pitch used is anthracite.
[0052] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0053] Comparative Example 1 1. Preparation of coal tar pitch-based carbon material: Untreated coal tar pitch is carbonized at 1200 °C under nitrogen gas and kept warm for 2 h under this condition with a heating rate of 5 °C / min to obtain a coal tar pitch-based carbon material.
[0054] 2. Preparation of sodium ion batteries: (1) Grind the coal tar-based carbon material, acetylene black and binder PVDF prepared in step 1 in a mortar at a mass ratio of 8:1:1, then add 1-methyl-2-pyrrolidone solution until the powder is a black viscous slurry for later use; (2) Using a 100 μm scraper, the slurry obtained in step (1) is evenly coated on a copper foil, and then the copper foil is dried at 60° C. for 6 h, and finally punched into a circular electrode sheet with a diameter of 12 mm, which is the negative electrode of the sodium ion battery; (3) The electrode sheet obtained in step (2) is used as the negative electrode, sodium metal is used as the positive electrode, glass fiber is used as the separator, 1MNaPF6 is used as the electrolyte, and the voltage range is 0.01~3 V to prepare a sodium ion battery.
[0055] Performance Testing Figure 1From the XRD patterns of the asphalt-based porous hard carbon material prepared in Example 1 and the coal tar-based carbon material prepared in Comparative Example 1, it can be seen that the XRD spectrum of the porous hard carbon material has two broad diffraction peaks at 25° and 43°, which are typical diffraction peaks of hard carbon in the (002) and (100) crystal planes.
[0056] Figure 2 The SEM images of the asphalt-based porous hard carbon material prepared in Example 1 and the coal asphalt-based carbon material prepared in Comparative Example 1 show that Comparative Example 1 is composed of irregular micron-sized particles (10-20 μm). Further observation shows that the surface is smoother and has a small amount of larger nanoparticles attached, with no developed pore structure ( Figure 2 Figure a, Figure b). The morphology of Example 1 is composed of irregular micron-sized particles (3-10 μm). Further, the enlarged SEM shows that ( Figure 2 (c, d) The surface is composed of nanoparticles (30-50 nm) stacked together, with abundant and open pores between the nanoparticles. This structure increases its specific surface area, is more conducive to ion transmission and electrolyte infiltration, and increases the physical effective contact area between the electrode material and the electrolyte.
[0057] The electrochemical performance was tested in the voltage range of 0.01–3 V. Figure 3 The charge and discharge curves of the first cycle of the batteries prepared in Example 1, Example 4 and Comparative Example 1 at 0.1 A / g show that compared with the coal tar-based carbon material (Comparative Example 1), the porous hard carbon materials with different catalyst addition amounts (Example 1 and Example 4) have improved the capacity of the sodium ion battery.
[0058] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.
[0059] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.
[0060] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.
Claims
1. A method for preparing a pitch-based porous hard carbon material, characterized in that: The preparation method comprises: mixing coal tar pitch, petroleum tar pitch and a catalyst to obtain a mixed asphalt, wherein the catalyst is p-toluenesulfonic acid, and then carbonizing the mixed asphalt to obtain an asphalt-based porous hard carbon material.
2. The method according to claim 1, characterized in that The coal tar pitch, petroleum tar pitch and catalyst are mixed and reacted in a solvent, wherein the solvent is toluene; the product after the mixed reaction is added into glycerol to evaporate the toluene, thereby obtaining a mixed asphalt after the toluene is removed.
3. The method according to claim 1, characterized in that The mass ratio of the coal tar pitch, petroleum tar pitch and catalyst is 1 g:(0.2-0.6) g:(0.01-0.03) g; The coal tar pitch is derived from lignite, bituminous coal or anthracite; the petroleum asphalt is derived from petroleum.
4. The preparation method according to claim 2, characterized in that: The mass volume ratio of mixed asphalt and toluene is 1 g:(10-50) mL; The temperature for evaporating toluene is 120-150°C.
5. The method according to claim 1 or 2, characterized in that: The temperature of the mixed reaction of coal tar pitch, petroleum tar pitch and catalyst is 50-70°C; the time of the mixed reaction is 2-6 hours; The carbonization is carried out under an inert atmosphere, the carbonization temperature is 900-1300°C, the time is 1-4 h, and the heating rate is 3-10°C / min.
6. A pitch-based porous hard carbon material obtained by the method according to any one of claims 1 to 5.
7. Use of the asphalt-based porous hard carbon material according to claim 6 in sodium ion batteries.
8. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises the asphalt-based porous hard carbon material according to claim 6; The separator includes glass fiber or polypropylene microporous membrane; the electrolyte includes sodium hexafluorophosphate or sodium perchlorate; and the positive electrode is sodium metal.
9. The method for preparing a sodium ion battery according to claim 8, characterized in that: The preparation method comprises: 1) mixing the asphalt-based porous hard carbon material according to claim 6, a conductive agent, a binder and a solvent to obtain a slurry; coating the slurry on an electrode substrate and drying to obtain a negative electrode; 2) assembling the negative electrode obtained in step 1) with a positive electrode, a separator and an electrolyte to obtain a sodium ion battery.
10. The method for preparing a sodium ion battery according to claim 9, characterized in that: In step 1), the drying temperature is 50-60°C and the drying time is 6-24 hours; The mass ratio of the asphalt-based porous hard carbon material, the conductive agent and the binder in step 1) is 8:(0.8-1.2):(0.8-1.2); The conductive agent is carbon black, conductive graphite, carbon tube, graphene, Ketjen black or acetylene black; The binder is polyvinylidene fluoride, styrene-butadiene rubber latex or carboxymethyl cellulose; The solvent is 1-methyl-2-pyrrolidone or water.
Citation Information
Cited By
Preparation method and application of high-purity pitch-based hard carbon based on coal pitch polycondensation impurity removal
CN120463183A